PERAN BALI PROCESS ON PEOPLE SMUGGLING, TRAFICKING IN PERSON AND RELATED TRANSNATIONAL CRIME (BALI PROCESS) DALAM MENANGANI PENYELUNDUPAN MANUSIA DI INDONESIA PADA TAHUN 2008-2013 - Ferica Wardani; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The focus of this research is the role of Bali process in dealing with people smuggling in Indonesia. People smuggling into today's complex problems. Human smuggling is a crime that is relatively favorable for the syndicate smugglers. It is estimated that annually can produce five to ten million dollars. Indonesia is a transit country for illegal immigrants who want to go to Australia. Not only a transit country, Indonesia has also become a destination country for illegal immigrants. From year to year, illegal immigration and people smuggling to Indonesia increased. This is evident from the facts obtained indicate that illegal methods most frequently used and the choice of the migration process.The problems of people smuggling can not be handled by a single country. For that Indonesia, together with Australia initiated of the Bali Regional Ministerial Meeting on People Smuggling, Trafficking in Persons and Related Transnational Crime in 2002. The meeting discussed about transnational crime lately increasingly troublesome countries affected. The meeting then produce a Regional Consultative Process, known as the Bali Process on People Smuggling, Trafficking in Persons and Related Transnational Crime or shortened by the Bali Process.Keywords: Bali Process, irregular migration, people smuggling,